Outcomes of pulmonary endarterectomy for patients with pulmonary artery sarcoma - Zhang, Zhaohua; Zhen, Yanan; Liu, Jingwen; Liu, Xiaopeng; Yang, Liang; Xu, Mingyuan; Wen, Jianyan; Liu, Peng (Frontiers in Cardiovascular Medicine, 2024)
Objective Pulmonary artery sarcoma (PAS) is an exceedingly rare and insufficiently investigated disease, leading to uncertain in its optimal management. This study aims to present our institutional experience and the outcomes of pulmonary endarterectomy for PAS. Methods We gathered clinical characteristics, intraoperative data, postoperative outcomes, and prognosis information from PAS patients who underwent surgical treatment at our institution between December 2016 and September 2023. Results A total of 20 patients with PAS underwent pulmonary endarterectomy. The median age of the patients was 52 (IQR 45, 57) years, with 12 patients (60%) being female. Intimal sarcoma was confirmed in 19 patients, while the remaining one was diagnosed with large cell neuroendocrine carcinoma. The perioperative mortality rate was three cases (15%). Follow-up was conducted for a median duration of 14 months (range: 1–61). During the follow-up period, 11 patients experienced recurrence or metastasis, and 5 patients succumbed to the disease. The estimated cumulative survival rates at 1 and 2 years for all 20 patients were 66.4% and 55.3%, respectively. Conclusion Pulmonary endarterectomy emerges as a palliative but effective approach for managing PAS, particularly when complemented with postoperative therapies such as chemotherapy and targeted therapy, which collectively contribute to achieving favorable long-term survival outcomes.